Unsur-Unsur Intrinsik dan Karaktetistik Sastra Anak Pada Cerita Terbentuknya Nama Lebong - Afifah, Aras Adzro; Anggraini, Dwi; Yuliantini, Nani (JURIDIKDAS, 2024)
The research aims to describe the intrinsic aspects related to the theme, plot, setting, characters, and moral values in the story "Terbentuknya Nama Lebong" from the book "Cerita Rakyat Rejang by Ekorusyono and Rosyadi. The research method used is qualitative descriptive with the subject of the research being the book itself. The researcher serves as the main instrument, supported by a descriptive story guide. The story follows the theme of cooperation and sacrifice, with the main characters being the Four Bikhus: Biku Sepanjang Jiwo, Biku Bembo, Biku Bejenggo, and Biku Bermano, as well as additional characters such as the white monkey, seven teenage girls, and their children. The setting is in the Renah Seklawi region in the past, with a social context influenced by social status and spiritual beliefs. The plot follows a progressive path, while the moral values revolve around unity and sacrifice as a means to overcome challenges and disasters. In line with the characteristics of children's literature, the story avoids sensitive topics such as sexuality, hatred, or violence. The simple presentation of the story makes it easier for children to understand the moral message, and allows them to apply it in their daily lives. In conclusion, "Terbentuknya Nama Lebong" is suitable for children's literature and contributes to the understanding of moral values through a narrative that can be enjoyed by readers.